College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter R - Section R.3 - Polynomials - R.3 Exercises: 15



Work Step by Step

-$(4m^{3}n^{0})^{2}$ = -($4^{2}$)$(m^{3})^{2}$$(n^{0})^{2}$ = -16$m^{3*2}$$n^{0*2}$ = -16$m^{6}$$n^{0}$ = -16$m^{6}$*1 = -16$m^{6}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.